MANUSIA DAN KEDUDUKANNYA: Pemikiran Alfred North Whitehead tentang Antropologi - Siti Saudah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2015)
Whitehead‟s thought is fundamental issues that interest andinfluence over the years. This leads to be categorized as a contemporaryphilosophy. Whitehead‟s thought about human being and his positionis described as follows: (1) Human being is a part of nature; accordingto Whitehead, human body and the surrounding world are closelyrelated and real. (2) Human being is Dynamic Creatures; according toWhitehead, the essence of one's existence lies in how active, howcreative, and how innovative he is in using his past for a newmanifestation of his life which gives the intensity of life experiencesmore deeply. (3) Human being Lives From and For Others; accordingto Whitehead, it refers to a “transition" or macroscopic process.Building relations with others is not only something that is accidental,but also something that is essential for every provider.I. Pendahuluan